(untitled) (Bangladesh Journal of Zoology, 2012)
About 185 leather processing industries have been operating in Hazaribagh and discharging solid and liquid wastes to the downstream areas of the river Buriganga and to the canals around. The physico-chemical parameters and biological examination of tannery effluents sewage water were carried out in relation to phytoplankton abundance at four selected points (viz. Kamrangirchar: K1, K2 and K3; Hazaribagh Tempo Stand: H) of the Buriganga river from October 2009 to September 2010. Altogether 27 genera of Phytoplankton belonging to the families Cyanophyceae, Bacillariophyceae, Chlorophyceae, Euglenophyceae and Cryptophyceae were identified from the above points. Merismopedia was the most abundant form (3.6×104 - 2.4×106 cell/L) compared to those (1.4-72 ×103 cell/l) genera of other phytoplankton (Nitzschia, Synedra, Pleurosigma, Euglena , Strusastrum, Crucigenia, Ourococcus ) at K1, the station closest to the tannery effluent outfall. The abundance of Merismopedia increased gradually (K2: 6.45×104 - 3.68×106, K3: 6.95×104 -1.68x107 and H: 1.0×105 - 2.06×107) along with the decreasing pollutant concentrations of the water. DOI: http://dx.doi.org/10.3329/bjz.v40i1.12901 Bangladesh J. Zool. 40(1): 121-128, 2012